Generating Flow Based on Dependencies - Varol, Nurhayat (Ieee, 2018)
This study presents a dependency based mapping approach to automate the process of generating a flow. A flow is a customized sequence of operators that transforms one set of data items into a more refined set based on a set of rules. First, the classification of various operators is carried out based on their usage in generating different flows. Based on this classification a flow generating algorithm is provided. An example follows to describe the central idea of the algorithm. Then, a few future enhancements of the study are proposed.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: Business Language; Dependency; Flow Automation; Flow Generation; Workflow